Multimedia files signature analysis in Blackberry Z10 - Abdullah@Selimun, Mohd. Taufik; Udzir, Nur Izura; Mahmod, Ramlan; Farjamfar, Anahita (Asian Network for Scientific Information, 2015)
Now-a-days, wide range of Smartphone models are available in the market which have a potentially extensive use in criminal activities. Smartphones as ever present devices, capable of connecting to the Internet and transferring huge amount of multimedia files have been identified as growing challenges to digital forensic investigators. One area of difficulty is to determine whether multimedia files collected form a Smartphone are created locally on the phone under examination or obtained from elsewhere. Using Blackberry Z10 as a case study, study was conducted to determine the system-generated artefacts on multimedia files when created by means of this Smartphone. By determining the metadata on these files, it contributed to a better understanding of the types of artefacts that are likely to be found by digital forensics practitioners and examiners. Potential identified findings include date and time of file creation, Operating System (OS) name and version, device name and other obscure metadata which could relate the file to this specific Smartphone.